2020
DOI: 10.1109/access.2020.3024682
|View full text |Cite
|
Sign up to set email alerts
|

Design of Filtering Crossover and Diplexer on SIW Quadruple-Mode Resonators in a Single Cavity

Abstract: This paper at first presents the proposal and design of a filtering crossover and diplexer with two second-order filtering channels on substrate integrated waveguide (SIW) quadruple-mode resonators (QMRs) and in a respective single cavity. The proposed method has an interesting application in the overall size miniaturization design. The proposed resonator is yielded with four perturbed modes, TE103, TE104, TE201 and TE202, and featuring distinct electric field distribution, by inserting metal via-holes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Coupling coefficients between two proposed cavities controlled by the CPW sizes at the feeding ports. 6 The coupling coefficient method in Reference2 is utilized to determine the parameters of the two coupling mechanisms. Figure 5 plots the coupling coefficients versus varied l c1 and l e1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupling coefficients between two proposed cavities controlled by the CPW sizes at the feeding ports. 6 The coupling coefficient method in Reference2 is utilized to determine the parameters of the two coupling mechanisms. Figure 5 plots the coupling coefficients versus varied l c1 and l e1 .…”
Section: Resultsmentioning
confidence: 99%
“…1 At present, substrate integrate waveguide (SIW) technology has gradually been widely used in designing filtering crossovers owing to the merits of low cost, high Q factor and easy integration. [2][3][4][5][6] Nevertheless, the filter transmission responses of the reported SIW crossovers are concentrated in single passband. Until now, to the best of authors' knowledge, there has been no multi-band SIW filtering crossovers been reported, and thus, it is eager to implement the SIW multi-band filtering crossovers for multi-band communication system applications.…”
Section: Introductionmentioning
confidence: 97%
“…Besides the above-mentioned dual-band BPFs, a three-state SIW diplexer with flexibly controlled CFs was proposed and reported in [129] with three input/output ports fed at specific positions of a single cavity operating with quadruple modes of TE 102 /TE 201 /TE 103 /TE 202 based on this kind of scheme. Additionally, a higher-order SIW diplexer was also developed and presented in [130] based on a single slots-perturbed quadruple-mode cavity, as the last circuit prototype shown in Fig. 14.…”
Section: F Activities Based On Single Multimode-resonator Schemementioning
confidence: 99%
“…For this reason, the researchers have suggested the use of orthogonal dual modes TE 201 and TE 102 of the SIW cavity to achieve different passband transmission by making the resonant frequency inconsistent through a reasonable design 18,19 . Multiple different TE modes are used, 20 which can significantly increase the frequency ratio of the two passbands. Additionally, the three‐dimensional (3D) structure based on three orthogonal modes TM 101x , TM 101y , and TM 101z allow for transmissions within three different channels 21,22 .…”
Section: Introductionmentioning
confidence: 99%